Hospitality’s ethical values and unethical employee behaviour: The mediating roles of work values and the moderating role of perceived organisational support - Chen, Qiuping; Liu, Zijuan (Frontiers in Psychology, 2022)
In recent years, hotels have occasionally engaged in unethical behaviour. This has become an urgent problem that requires a solution. Based on social exchange theory, this study constructs a theoretical model of the relationship between hospitality’s ethical values and unethical behaviour. According to 543 questionnaires, the findings indicate that hospitality’s ethical values negatively affect the unethical behaviour of employees. Work values played a part in the intermediary role between the two, and perceived organisational support significantly positively regulated the relationship between hospitality’s ethical values and unethical behaviour. By exploring the logical relationship between hotels’ and employees’ morality, this study expands the research content and theoretical framework of unethical employee behaviour and helps to bridge the work values of hotels and individuals. Furthermore, it helps to build a good hotel ethical value system, which can effectively reduce and suppress the emergence of unethical employee behaviour.